Efficiency limits for photoelectrochemical water-splitting - Katherine T. Fountaine (Nature Portfolio, 2016)
Theoretical limiting efficiencies play a critical role in determining technological viability and expectations for device prototypes. Here, the authors present a unified framework for photoelectrochemical device performance through which previous limiting efficiencies can be understood and contextualized.